Hybrid polymeric systems: Design, biomedical applications, Opportunities, Challenges and Future Perspectives - Chapa, Christian (Woodhead Publishing, ELSEVIER, 2024)
Hybrid polymeric systems have emerged as an area of interest for scientific research and development in many areas of biomedical engineering and medicine. Hybrid polymeric systems involve a combination of two or more materials of polymeric nature where each contributes its own properties and functionalities acting in synergy in an integrated structure. The resulting hybrid polymeric systems consequently exhibit improved performance. This opens up a wide range of properties that can be modulated according to the specific biomedical application. It should be remembered that the structure of materials governs their properties, so two different polymer structures will have two or more different properties that will act on the resulting hybrid system. Hybrid polymeric systems have several advantages, including the versatility in design and composition that can be achieved. However, researchers must carefully select and combine these polymers to achieve the desired performance. Hybrid polymeric systems can be designed to achieve specific characteristics such as improved mechanical strength, compatibility with physiological fluids, biodegradability or other properties that respond to environmental stimuli. We are facing the development of advanced materials of polymeric nature that interact with biological systems and a great possibility of biomedical applications opens.